2005
DOI: 10.1108/09596110510612149
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing financial performance of small hotels in Tanzania

Abstract: PurposeThe purpose of this paper was to investigate the factors influencing financial performance of small hotels, particularly in developing countries like Tanzania.Design/methodology/approachThis investigation used financial ratio analysis on business performance data collected from small hotels in Tanzania through face‐to‐face interviews. Currently there is no existing data on such aspects of the hotel industry in Tanzania. As a consequence, Arusha region was selected as the sample for this study due to a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 15 publications
2
50
2
2
Order By: Relevance
“…Meanwhile, financial performance is appropriate and acceptable in comprehending organizational effectiveness, citing the many benefits that profitable and well-run companies provided for the society and for their relevant stakeholders (Randolph and Dess, 1984;Snow and Hambrick, 1980). Sharma and Upneja (2005) found that hotel performance is influenced by internal factors (i.e., employee training, investments in equipment, and availability of financing options) and external factors (i.e., institutional environments and product service standardization systems). Moreover, organizational assets (i.e., organizational structure and human resource management and policy) and reputational assets (i.e., company reputation, customer service reputation, and product reputation) are significantly and positively associated with hotel performance.…”
Section: Hotel Performancementioning
confidence: 98%
See 1 more Smart Citation
“…Meanwhile, financial performance is appropriate and acceptable in comprehending organizational effectiveness, citing the many benefits that profitable and well-run companies provided for the society and for their relevant stakeholders (Randolph and Dess, 1984;Snow and Hambrick, 1980). Sharma and Upneja (2005) found that hotel performance is influenced by internal factors (i.e., employee training, investments in equipment, and availability of financing options) and external factors (i.e., institutional environments and product service standardization systems). Moreover, organizational assets (i.e., organizational structure and human resource management and policy) and reputational assets (i.e., company reputation, customer service reputation, and product reputation) are significantly and positively associated with hotel performance.…”
Section: Hotel Performancementioning
confidence: 98%
“…The attitudes and actions of employees affect the success of a hotel service encounter. Sharma and Upneja (2005) indicated that the financial performance of hotel operations is crucially dependent on formal education and technical training of front-line employees. In the other words, hotel employees are the main factors driving the differentiating services to customers, which lead to superior performance (Bowen and Chen, 2001).…”
Section: Hotel Performancementioning
confidence: 99%
“…In Australia, respondents with university education form only 34% (Getz and Carlsen, 2000) and 31.8% (Sharma and Upneja, 2005) of the total. However, Glancey and Pettigrew (1997) find that there is an equal balance between respondents with secondary education and those with universitylevel education in Scotland.…”
Section: Demographic Profilementioning
confidence: 99%
“…The most popular components of the profile of the owners/managers are age and sex (Ateljevic et al, 1999;Szivas, 2001;Ahmad, 2005;Sharma and Upneja, 2005), education (Glancey and Pettigrew, 1997;Avcikurt, 2003;Sharma and Upneja, 2005), work experience (Ateljevic et al, 1999;Szivas, 2001), and marital status (Getz and Carlsen, 2000). The dominant age of small business owners/managers is in the category of middle-age and older, that is, 25-50 (Avcikurt, 2003), 30-45 (Ahmad, 2005), and 45 and older (Szivas, 2001;Getz and Carlsen, 2000).…”
Section: Demographic Profilementioning
confidence: 99%
“…Four performance indicators were chosen: financial, internal business, customer perspective, and learning perspective for green hotels [39,[41][42][43]. Financial performance includes financial ratios, stock prices and/or risk, market sales, and financial margins.…”
Section: Performance Indicatorsmentioning
confidence: 99%